Last of the empires : a history of the Soviet Union ; 1945 - 1991 - Keep, John L. H., 1926- 1926- (Oxford Univ. Press, 1995)
In this book, John Keep gives a narrative history of the USSR from the last years of Stalin's despotic rule to the eventual collapse of the empire in 1991. During these years living standards slowly improved as various attempts were made to reform Communist rule. Although material prosperity rose under Khrushchev and Brezhnev, however, the Communist system itself began to erode. The official ideology grew less and less relevant to people's everyday concerns; the Party lost its moral authority. The early 1980s saw a growing black market economy, incompetent management, and agricultural waste. When control passed to pragmatic, younger leaders like Gorbachev, their attempts to reinvigorate the economy by appealing to the intelligentsia opened a Pandora's box of conflicting opinions. The Party surrendered its monopoly of power, central institutions crumbled, and the centrifugal forces emanating from national minorities culminated in the empire's downfall